2015
DOI: 10.18632/oncotarget.4573
|View full text |Cite
|
Sign up to set email alerts
|

NOP14 suppresses breast cancer progression by inhibiting NRIP1/Wnt/β-catenin pathway

Abstract: NOP14, which is functionally conserved among eukaryotes, has been implicated in cancer development. Here, we show that NOP14 is poorly expressed in breast cancer cells and invasive breast cancer tissues. In vivo and in vitro studies indicated that NOP14 suppressed the tumorigenesis and metastasis of breast cancer cells. Further investigations revealed that NOP14 enhanced ERα expression and inhibited the Wnt/β-catenin pathway by up-regulating NRIP1 expression. Survival analysis indicated that low NOP14 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 33 publications
(34 reference statements)
1
32
0
Order By: Relevance
“…A previous study demonstrated that NOP14 enhances the stability of mutp53, enabling mutp53 to participate in the progression of pancreatic cancer . NOP14 could suppress cancer metastasis by regulating the Wnt/β‐catenin signalling pathway in cancers . In our research, we found that NOP14 is involved in cell proliferation and migration and induces apoptosis in BCa cells.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…A previous study demonstrated that NOP14 enhances the stability of mutp53, enabling mutp53 to participate in the progression of pancreatic cancer . NOP14 could suppress cancer metastasis by regulating the Wnt/β‐catenin signalling pathway in cancers . In our research, we found that NOP14 is involved in cell proliferation and migration and induces apoptosis in BCa cells.…”
Section: Discussionsupporting
confidence: 60%
“…35 NOP14 could suppress cancer metastasis by regulating the Wnt/β-catenin signalling pathway in cancers. 36,37 In our research, we found that NOP14 is involved in cell proliferation and migration and induces apoptosis in BCa cells. Furthermore, NOP14 silencing reduced the expression of cell cycle-related proteins and MMP9 and upregulated the expression of cleaved Caspase 3.…”
Section: Discussionmentioning
confidence: 56%
“…Wnt/β-catenin signaling has been shown to play an important role in the development and promotion of into the nucleus of breast cancer cells. Additionally, in ER-positive breast cancers, NOP14 increase the level of ERα via NRIP1, implied that NOP14 can suppress breast cancer by inhibiting the Wnt/ β-catenin pathways possibly by up-regulating NRIP1 [25]. These findings provide new hope of developing targeted therapies against NOP14 and NRIP1 for breast cancer.…”
Section: Introductionmentioning
confidence: 82%
“…Eleven of the 12 sites were differentially edited including AZIN1 S367G , highlighting the importance of AZIN1 RNA editing in cancer development. The top 3 edited genes were NOP14 I779V (chr4:2,938,299), FLNB M2324V (chr3: 58,156,064), and IGFBP7 K95R (chr4: 57,110,068), all of which have been suggested to suppress breast cancer progression (26)(27)(28). Moreover, DNA mutations of NOP14 I779V and FLNB M2324V are reported in COSMIC (29), demonstrating the utility of TCEA to identify driver-like editing events in carcinogenesis.…”
Section: Edcancer Modulementioning
confidence: 94%